Dolly’s Ribs. For a Semiotics of Cultured Meat - Vanacore, Beatrice (E|C, 2025)
The advent of cultured meat has provoked wide-ranging debates in the food, ethical and political spheres. This new commodity genre, produced by growing animal cells in bioreactors instead of slaughtering animals, does not differ nutritionally from conventional meat, but raises questions about its cultural and natural status. Despite the ethical and environmental benefits of cultured meat, such as reduced CO2 emissions and animal protection, the introduction of this innovative food is opposed by many governments, including Italy. The debate, which goes beyond the food sphere, touches on political, social and cultural aspects, creating a dichotomy between the supporters of cultured meat, who extol its sustainability and innovation, and its detractors, who fear its artificiality and possible risks. The aim of this essay is to explore how cultured meat is portrayed in public discourse, both in its promotion and criticism, by analysing the terminologies used and the political and social rhetoric related to it. The analysis of various examples, including Italian and US positions, offers insight into the cultural and political dynamics that influence its entry into the market, raising questions about what really defines the concept of Nature and Culture in the contemporary context.